Tumor BRCA testing can reveal a high tumor mutational burden related to POLE pathogenic variants - M.-C. Villy; J. Masliah-Planchon; S. Melaabi; O. Trabelsi Grati; E. Girard; G. Bataillon; A. Vincent-Salomon; J. Le Gall; L. Golmard; D. Stoppa-Lyonnet; I. Bieche; C. Colas (Elsevier, 2021)
Objective: Tumors harboring a POLE pathogenic variant, associated with high tumor mutational burden, are good candidates for immunotherapy. However, POLE pathogenic variants are not currently screened in routine clinical practice. Can these tumors be identified by means of an already available test? Methods: We describe seven tumors harboring a POLE pathogenic variant, among eight patients with tumors harboring multiple BRCA1/2 variants (from 4 to 20). All patients were managed at Institut Curie, Paris. Five patients were selected because of unexpected tumor BRCA testing results with multiple variants and another three patients were selected because of a POLE pathogenic variant detected by large tumor testing. We looked for other tumor variants by Next-Generation Sequencing in tumors harboring multiple BRCA1/2 variants, and for multiple BRCA1/2 variants in tumors harboring a POLE pathogenic variant. Results: Four of the five tumors selected because of multiple BRCA1/2 variants exhibited a POLE pathogenic variant, and all three tumors selected for POLE pathogenic variants exhibited multiple BRCA1/2 variants. Conclusions: Tumor BRCA testing could be a way to detect tumors harboring a highly mutagenic POLE pathogenic variant.